Convergence and Divergence Analysis in Islamic Financing - Ihdina Sabilal Haq; Sri Herianingrum (AFEBI Islamic Finance and Economic Review, 2019)
This study aims to determine the convergence and divergence between the theory and practice of Mudaraba and Musyaraka financing in Islamic Banking. The method used in this study is a combination of reviewing the existing literature and critical analysis of the results of several relevant studies to analyze the convergence or divergence between the theory and practice of Mudaraba and Musyaraka financing in Islamic Banking. The findings show that the divergence in the financing of Mudaraba and Musyaraka contracts tends to be less than the convergence. This can be caused by the times and the different needs of these developments, so there is a need for innovation and diversification of Mudaraba and Musyaraka financing which makes it slightly different between practice and theory.